Questioning Indonesia's Role in Addressing Rohingya Refugees: A Legal, Humanitarian, and State Responsibility Perspective - Sudrajat, Tedi; Hidayat Jati, Baginda Khalid; Gupta, Chander Mohan (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2024)
This article discusses Indonesia’s involvement in addressing the plight of the Rohingya refugees, who have been deprived of citizenship, leading to the erosion of their basic human rights. This deprivation has resulted in widespread social exclusion and displacement, forcing many to seek asylum in countries like Indonesia. Therefore, this study aims to: firstly, analyze the legal framework within which international law enables the Indonesian government to responsibly manage refugee situation; and secondly, evaluate the collective efforts of the Indonesian government and the global community in seeking a comprehensive resolution to this crisis. The paper focuses on the legal dimensions of the Rohingya refugee situation in Indonesia, employing a normative approach. It offers a descriptive analysis from the perspective of governance and international law. The findings emphasize the need for the Indonesian government to adopt a proactive stance. Key measures include advocating for the Rohingya's right to citizenship, urging the Myanmar government to halt its violence, and calling for active intervention from the United Nations (UN) and the international community. Furthermore, it is recommended that Indonesia continues to offer temporary refuge on humanitarian grounds, ensuring the provision of aid and adhering to the principle of non-refoulement. Effective coordination among local and central governments, as well as international partners, is essential for the strategic management of refugee issues.